Developing A Board Game-Based Supplementary Learning Material Prototype for Accounting - Sila Ninin Wisnantiasri; Paramitha, Diky; Hidayah, Putri Agustina (Journal of Science and Education (JSE), 2024)
The most effective approach for educators is to provide students with the knowledge and enhance their motivation to study, employ diverse pedagogical approaches shifted away from one-way teaching approaches, and prioritized students’ needs by encompassing innovation tools such as the utilization of board games. This research aims to develop a prototype of an interactive board game as a supplementary tool for learning accounting. The game focuses on preparing financial reports and is designed to provide a practical learning experience in the field of business. This research utilized the waterfall model in research and development (R&D). Prototyping consists of communication, planning, design, construction, and distribution stages. During the communication stage, user requirements are elucidated through interviews with prospective users, observations of business practices, and examinations of relevant literature. Preliminary interview findings from culinary entrepreneurs indicate the challenges in preparing financial statements, which hinder their ability to communicate business performance and secure finances. The user's needs have been determined, and specific activities, timelines, resources, and budgets are set. The research employed an iterative prototyping approach in the prototype design process, wherein a sequence of tests is conducted consecutively to refine the prototype. In the production phase, the prototype is tested and assessed based on comments obtained during playtest sessions, with results satisfying testimonials. The advice received from students about the time limitation of the games was because of the complexity of accounting transactions, and then the games were modified by providing the spreadsheet version of the journal form that can be accessed from the barcode. This instructional tool was developed to enhance the efficacy of learning techniques, particularly in comprehending and mastering the accounting process, whether pursued individually or in a collaborative setting; hence, for the next research, we can transform this game into digital games to make it more interesting.